Investigating the corporate debt and real investment nexus: dynamics and challenges in a shifting financial landscape - Bashir Ahmad JOO; Simtiha Ishaq MIR (Theoretical and Applied Economics)

(untitled)
This paper studies the interrelationship between corporate debt and Real Investment in view of the pivotal role played by private debt in economic growth and development. With a focus on the financial intricacies and upcoming challenges faced by emerging markets, this paper investigates how corporate debt influences and shapes gross capital formation within emerging economies. The study finds a negative relation between the two variables with a one per cent increase in corporate debt to GDP ratio resulting in about 4 per cent decline in real investment in the short run and long run. Trade openness however has a positive coefficient, indicating that it has a stimulating impact on real investment within the economy. Through a comprehensive analysis, the study not only contributes to the existing body of knowledge but also offers valuable insights for crafting effective financial policies tailored to the unique challenges of these evolving markets.